2007
DOI: 10.1111/j.1447-0756.2007.00569.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiles in serum and peritoneal fluid from infertile women with and without endometriosis

Abstract: The elevated levels of MCP-1, IL-6, and IL-8 in peritoneal fluid but not serum may indicate the importance of local macrophage activating factors in the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
111
2
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(135 citation statements)
references
References 21 publications
13
111
2
9
Order By: Relevance
“…Increased serum IL-6 levels observed in patients with minimal-mild endometriosis in our study are in line with findings of some reports [18][19][20] but depart from others that found no value for serum IL-6 in the diagnosis of endometriosis at any stage [21,22] and from yet others that reported slightly elevated serum IL-6 levels in controls [23][24][25]. Additionally, it is worthwhile to note that serum IL-6 was the only marker that was constantly elevated in all our comparison groups (endometriosis group, minimalmild endometriosis group and moderate-severe endometriosis group).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Increased serum IL-6 levels observed in patients with minimal-mild endometriosis in our study are in line with findings of some reports [18][19][20] but depart from others that found no value for serum IL-6 in the diagnosis of endometriosis at any stage [21,22] and from yet others that reported slightly elevated serum IL-6 levels in controls [23][24][25]. Additionally, it is worthwhile to note that serum IL-6 was the only marker that was constantly elevated in all our comparison groups (endometriosis group, minimalmild endometriosis group and moderate-severe endometriosis group).…”
Section: Discussionsupporting
confidence: 90%
“…had increased plasma concentrations of inflammatory cytokines. Comparable TNF-α [20,[23][24][25]] levels were previously reported in women with and without endometriosis. However, other investigators reported elevated levels of TNF-α and Epo in endometriosis patients compared with controls [13,18,26].…”
Section: Discussionmentioning
confidence: 64%
“…Primary cultures of endometriotic epithelial cells have been shown to produce IL-6, IL-8, and TNF-␣ (Bergqvist et al, 2000;Luk et al, 2005). MCP-1 and RAN-TES have also been found elevated in peritoneal fluid of women with endometriosis, and previously, their production has been reported to originate from stromal cells (Bersinger et al, 2006;Kalu et al, 2007). Results from our studies clearly demonstrate an effect of TNF-␣, a primary effector of inflammatory responses, to increase production of IL-6, IL-8, MCP-1, and GM-CSF from 12Z epithelial endometriotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion occurs by the activation of cell adhesion molecule sICAM-1, oxidative stress, and inflammatory processes which are supported by activated immune cells [19].…”
Section: Angiogenesismentioning
confidence: 99%